Co-movement and causality dynamics linkages between conventional and Islamic stock indexes in Bangladesh: A wavelet analysis - Mohammad Sahabuddin; Md. Farjin Hassan; Mosab I. Tabash; Mohammad Ahmad Al-Omari; Md. Kausar Alam; Fakir Tajul Islam (Cogent Business & Management, 2022)
The study examines the co-movement and dynamic causality between conventional and Islamic stock indexes in Bangladesh from 20 January 2014 to 31 August 2019. This study employs multi-scales and wavelet-based techniques in examining the co-movement and causality between variables. The results reveal that the co-movement between Islamic and conventional stock indexes is very high in the long run. Furthermore, the results of this study indicate that there is a lead-lag relationship between Islamic and conventional index using wavelet-based decomposed Granger Causality methods. The results point out that the causality varies in time and scales domain properties. However, the Dhaka Stock Exchange Shariah Index (DSES) shows significant influences on DSEX and creates a bidirectional causality for the selected brand scales over the study period. The findings contribute to the existing literature by adding new evidence on the co-movement and causality linkages between Islamic and conventional stock indexes and provide one more index for gaining portfolio diversification benefits among national and international investors.
Keywords: 650; Bangladesh; causality; Co-movement; Islamic and conventional stock indexes